(untitled) (The Review of Diabetic Studies, 2025)
Radiation exposure from medical and environmental sources represents a significant public health concern due to its potential to cause acute biological damage and chronic diseases. This systematic review synthesizes global evidence on short-term and long-term health effects associated with ionizing and non-ionizing radiation exposure. Data were gathered from epidemiological, clinical, environmental, and occupational studies published between 2010 and 2025. Findings demonstrate that medical imaging—particularly CT scans—remains a major contributor to artificial radiation exposure, while environmental sources such as radon, ultraviolet radiation, and nuclear accidents continue to pose persistent global risks. Short-term health effects include acute radiation syndrome, inflammation, and cellular dysfunction, whereas long-term consequences encompass carcinogenesis, cataracts, cardiovascular disease, and heritable genetic mutations. The review further examines global dose monitoring frameworks and evaluates mitigation strategies, including dose optimization, environmental surveillance, public-health education, and international regulatory standards. Evidence highlights the need for improved risk–benefit communication, reduced unnecessary imaging, strengthened occupational protection, and global harmonization of radiation safety policies. This comprehensive evaluation supports efforts to balance technological benefits with population safety in healthcare and environmental contexts.